Il modello BIM: una copia reale del progetto (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The tools we use affect our choices and the product of our research. Around this assumption the paper try to investigate how the introduction of a new way to face architectural project can affect the project itself and the role of the architect. The introduction of the drawings as the authorial mark of the architect, this new professional figure born with Leon Battista Alberti, affected the way architecture was thought and built after Middle Ages. The diffusion of BIM in this late decade open the question: is it just a new tool for drawing, keeping the tradition we – as architects – have always looked for since Alberti, or open a different way to operate in the design process that can impact our choices and our role? The way to investigate is to reason about the model, as product of the Building Information Modeling, and its particularly potentials.